Mixed matrix membranes containing fluorescent coordination polymers for detecting Cr2O72− with high sensitivity, stability and recyclability. Issue 23 (7th June 2021) - Xu, Yong-Kai; Meng, Mei-Mei; Xi, Ji-Ming; Wang, Li-Fei; Zhu, Rui; Liu, Xing-Gui; Zhang, Rui; Dong, Wei; Lu, Zhen-Zhong; Zheng, He-Gen; Huang, Wei
Abstract : Mixed matrix membranes (MMMs) containing fluorescent coordination polymers (CPs) showed high sensitivity and selectivity for detecting Cr2 O7 2− in water. Both recyclability and stability of the MMMs were remarkably higher than those of CP powders. Abstract : Three coordination polymers (CPs) were synthesized by using Cd II, fluorescent 9, 10-di(4-pyridyl)anthracene ( dpa ), and cyclohexane-1, 4-dicarboxylic acid (H2 cda ), and they are [Cd2 ( dpa )2 ( cda )Cl2 ] n (1 ), [Cd( dpa )2 ( cda )] n (2 ) and [Cd( dpa )( cda )(H2 O)] n (3 ). Both 1 and 2 are fluorescent and contain nonporous layers. 3 is an isomer of 2 and contains a porous diamondoid network. Fluorescent mixed matrix membranes were prepared by dispersing the particles of 1 or 2 within the matrix of polymethyl methacrylate, and showed high sensitivity and selectivity for detecting Cr2 O7 2− in water. Both stability and recyclability of the MMMs were remarkably higher than those of the CP powders.